The relationship between effective listening skills towards employee’s job performance at Pejabat Daerah Kemaman, Terengganu / Ristu Izana Kamaludin - Kamaludin, Ristu Izana (Faculty of Business And Management, 2014)
This research was about the effective listening skills that gave impacts towards the employee's job performance. The main objective was to study whether there was a relationship between the independent variable (effective listening skills) and dependent variable (employee's job performance). I was using the employees from middle and lower level management of Pejabat Daerah Kemaman as my sample for this research. From the population of this study, I have selected 10 per cent from the 100 employees in Pejabat Daerah Kemaman which was about 42 peoples as a sample size. For this research, I was using probability sampling which was simple random sampling. I was using this technique because it is a simple way to distribute questionnaires to the respondents. Thus, I used questionnaire as my method in order to conduct this research. 42 questionnaires have been distributed to the respondents and all of them have returned back the completed questionnaires. There were three section (Section A, B, and C) in the questionnaire and was developed in bilingual. I was using five-point likert scale to represent the respondent's response towards the questionnaires. Statistical Package of Social science (SPSS) software of Version 21 was being used to analyse the data. This study focused more on correlational research, so, the numerical index called correlation coefficient has been used to measure the relationship between variables. After the analysis has been done, I fmd that there is a significant relationship between effective listening skills towards employee's job performance. In addition, the findings of this research will let the middle and lower level employees knew about the positive impacts of effective listening skills that affect their job performance. As a conclusion, the employees of Pejabat Daerah Kemaman perceive the effective listening skills at their workplace. From the findings, I would like to recommend that they have to maintain the skills because listening skills can contribute to their work success and is a key of effective communication. By practising and using this skill continuously, their work will have higher quality and more effective.